2017
DOI: 10.1007/s40615-017-0446-x
|View full text |Cite
|
Sign up to set email alerts
|

African Americans, African Immigrants, and Afro-Caribbeans Differ in Social Determinants of Hypertension and Diabetes: Evidence from the National Health Interview Survey

Abstract: In the United States (U.S.), Blacks have higher morbidity and mortality from cardiovascular disease (CVD) than other racial groups. The Black racial group includes African Americans (AAs), African immigrants (AIs), and Afro-Caribbeans (ACs); however, little research examines how social determinants differentially influence CVD risk factors in each ethnic subgroup. We analyzed the 2010-2014 National Health Interview Survey, a cross-sectional, nationally representative survey of non-institutionalized civilians. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Given what we know about the relationships between social determinants of health, such as educational attainment and health outcomes, variations in characteristics of social determinants can have implications for health outcomes and for the appropriateness of standardized health interventions that do not consider the unique needs of certain populations (Marmot & Allen, 2014). In fact, there is some evidence suggesting that African Americans, African immigrants, and Afro-Caribbean immigrants, respectively, have unique social determinant characteristics that impact hypertension and diabetes prevalence (Commodore-Mensah et al, 2018). Both social and structural factors that heighten African immigrants' vulnerability to poor health outcomes warrant attention.…”
Section: Black African Immigrants and Health Researchmentioning
confidence: 99%
“…Given what we know about the relationships between social determinants of health, such as educational attainment and health outcomes, variations in characteristics of social determinants can have implications for health outcomes and for the appropriateness of standardized health interventions that do not consider the unique needs of certain populations (Marmot & Allen, 2014). In fact, there is some evidence suggesting that African Americans, African immigrants, and Afro-Caribbean immigrants, respectively, have unique social determinant characteristics that impact hypertension and diabetes prevalence (Commodore-Mensah et al, 2018). Both social and structural factors that heighten African immigrants' vulnerability to poor health outcomes warrant attention.…”
Section: Black African Immigrants and Health Researchmentioning
confidence: 99%
“…It is thus expected that immigrants who had a relatively low exposure to cardiovascular-risk factors in their countries of origin will take on high-risk behaviours from native population in host countries. Nevertheless, results from same levels of exposure to risk factors may vary in individuals or populations from different ethnical origins [30]. Several studies have identified differences in the prevalence of certain diseases related to cardiovascular risks and their subsequent complications in different ethnical groups.…”
Section: Sociodemographic Variables and Cardiovascular Riskmentioning
confidence: 99%
“…The challenge is that most epidemiological surveys, including National Health and Nutrition Examination Survey (NHANES), combine all foreign-born blacks into a single group. As African descent populations are diverse in culture, history, and genetics, there are differences in allostatic load triggers, as well as the etiology and presenting phenotype of diabetes and CVD [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%